The use of African medicinal plants in cancer management - Gaobotse, Goabaone; Venkataraman, Srividhya; Brown, Phenyo D.; Masisi, Kabo; Kwape, Tebogo E.; Nkwe, David O.; Rantong, Gaolathe; Makhzoum, Abdullah (Frontiers in Pharmacology, 2023)
Abstract Cancer is the third leading cause of premature death in sub-Saharan Africa. Plants continue to provide unlimited pharmacological bioactive compounds that are used to manage various illnesses, including cancer. By reviewing literature, we provide an inventory of plants with reported anticancer activity used in Africa and the evidence supporting their use in cancer management. In this review, we report numerous plants that have been used for cancer management in Africa, where the anticancer extracts are usually prepared from barks, fruits, leaves, roots, and stems of these plants. Extensive information is reported about the bioactive compounds present in these plants as well as their potential activity against various forms of cancer. However, information on the anticancer properties of other African medicinal plants is insufficient. Therefore, there is a need to isolate and evaluate the anticancer potential of the bioactive compounds in other African medicinal plants. Further studies on these plants will allow the elucidation of their anticancer mechanisms and allow the identification of phytochemicals that are responsible for their anticancer properties. Overall, this review provides consolidated and extensive information not only on diverse medicinal plants of Africa but on the different types of cancer that these plants are used to manage and the diverse mechanisms that are involved during cancer alleviation.